RARG Gene Dysregulation in Acute Myeloid Leukemia - Conserva, Maria Rosa; Redavid, Immacolata; Anelli, Luisa; Zagaria, Antonella; Specchia, Giorgina; Albano, Francesco (Frontiers in Molecular Biosciences, 2019)
Retinoic acid receptor γ (RARγ) belongs to the nuclear receptor superfamily and shares 90% homology with retinoic acid receptor α (RARα) and retinoic acid receptor β (RARβ). RARA rearrangements are well known to be involved in acute promyelocytic leukemia (APL), but RARG rearrangements can also resemble this kind of leukemia. In this review we trace the role of RARγ, considering both its physiological and oncogenic contribution; from 2011 to date, nine cases of patients harboring RARG fusions have been reported. These patients showed typical APL features, including the clinical presentation, coagulation abnormalities and morphological features of bone marrow (BM), but are not responsive to APL standard therapy. We stress the urgent need for a better comprehension of the critical role of RARG dysregulation in the leukemogenesis process, since optimum therapy strategies have not yet been established.